Linoleic Acid Induced Acute Hepatitis: A Case Report and Review of the Literature - Mohammad Bilal; Yogesh Patel; Micheal Burkitt; Michael Babich (Case Reports in Hepatology)
Several dietary supplements used for weight loss have been reported to cause hepatotoxicity. Conjugated Linoleic Acid (CLA) is a dietary supplement that has been shown to cause reduction in body fat mass. Here, we present the first case of CLA induced acute hepatitis in the United States and only the third case in the worldwide literature along with a brief review of the literature.